Culturally influenced risk exposure: A new approach to tackle risks in offshore outsourcing - Ramingwong S. (2014)
Culture is arguably perceived as the most influential risk factor in offshore outsourcing of software projects. Yet, due to its intangible characteristics, quantifying and systematizing this factor seems to be impracticable. This paper proposes a new approach to enhance risk assessment process by involving culture in the calculation. The results from this new approach suggest a better evaluation of risk which leads to more appropriate planning and mitigation. © 2011 IEEE.